Developing an emergent theoretical framework for artificial pseudo-gene communication pathway in DNA computing - Shamsudin, Ahmad Faizul; Suhaimi, Mohd Adam; M., Huweldi; Seth, Salam; N., Aishah; A. F., AlyaKhadijah; R., Hidayah; Noorbatcha, Ibrahim Ali (IEEE, 2012)
The extended information theory of Shannon with Feynman used in natural DNA computing is proposed to be used for artificial pseudo-gene computing. The theory predicts the performance in terms of information decays of the pseudo-gene communication system of information encoding, transmission and decoding similar to natural molecular reactions. An emergent theoretical framework for artificial pseudo-genes using cooperative multi-agents with gene motif binary switching algorithm is developed. The results indicated differences in information decays between artificial and natural DNA computing systems. Further development of the gene motif binary switch algorithm may achieve convergence between the artificial and natural systems